One in a million eaudiobook Journey to your promised land. - Shirer, Priscilla (christianaudio, 2018)
The Egyptians in Exodus 1 were intent on enslaving the Israelites, wearing them down so that God's chosen people would become disillusioned and not live up to their destiny. Of the original two million Israelites who received God's invitation to enter the Promised Land, only two actually entered it!Similarly, modern day Christians often hear and understand the promises of God each Sunday morning at church but then rarely choose to experience them in everyday life. In One in a Million, Bible teacher Priscilla Shirer invites us to change that pattern for good, living beyond our circumstances and expecting to see God move in miraculous ways day after day. Without a doubt, we can find and follow God's purpose for our journey. We can make it to the Promised Land!